The Role of Digital Inquiry-Based Learning in Enhancing Scientific Literacy and Student Engagement in Science Education - Utami, Ayu Rischi (Scientica Education Journal, 2024)
This study aims to examine the effectiveness of digital inquiry-based learning in enhancing students’ scientific literacy and engagement in science education. The research employed a quantitative approach using a quasi-experimental design with a non-equivalent control group. The participants consisted of two groups: an experimental group taught using digital inquiry-based learning and a control group taught using conventional methods. Data were collected through a scientific literacy test and a student engagement questionnaire. The results showed that the experimental group achieved significantly higher post-test scores compared to the control group. The normalized gain (N-gain) analysis indicated that the experimental group reached a medium to high level of improvement, while the control group remained in the low to medium category. Statistical testing using an independent sample t-test revealed a significant difference between the two groups (p < 0.05). In addition, digital inquiry-based learning significantly improved students’ behavioral, emotional, and cognitive engagement, with the highest improvement observed in cognitive engagement. These findings suggest that integrating digital technology with inquiry-based learning is an effective strategy to promote meaningful learning and develop essential 21st-century skills in science education.